Genotyping of white spot syndrome virus on wild and farm crustaceans from Sonora, Mexico - González Galaviz, José Reyes; Rodriguez Anaya, Libia; Molina Garza, Zinnia Judith; Ibarra Gámez, José Cuauhtémoc; Galaviz Silva, Lucio (2013)
White spot syndrome is a viral disease affecting wild and farm crustaceans that serve as reservoirs. Previous reports have demonstrated high genomic variation in WSS viruses (WSSV) isolated from distinct geographical regions. In this study, we collected wild shrimps (Litopenaeus stylirostris), crabs (Callinectes arcuatus) and farmed shrimp (L. vannamei) in Sonora, Mexico, between 2008 and 2010. DNA was extracted, and the variable regions and transposase genes were subjected to PCR and sequencing. Compared to strains of WSSV from other sites, Mexican samples exhibited a distinct number of repeat units (RUs) in ORF94, ORF75 and ORF125, which ranged between 1-11, 3-15, and 8-11 RUs respectively, and a unique single nucleotide polymorphism (SNP) at position 48 of ORF94. A total of six Mexican genotypes were found in organism from shrimp farm and natural environment.